Socio-Psychological Structure of Legal Relations - D. S. Beznosov (СибСкрипт)
A state governed by the rule of law relies on legal principles recognized and accepted by its society. To determine the socio-psychological structure of legal relations, the author compared the concept of legal relations in Western and Russian legal and social psychology. While Western publications contain no such concept whatsoever and focus mostly on interracial relations, Russian authors barely touch upon legal relations. The article introduces the main socio-psychological structure of legal relations and the term of legal social capital as an indicator of the support of state legislation by society. In the empirical part of the study, a survey of 467 respondents yielded a legal social capital of 0.805 (max 1.0). The socio-psychological structure of legal relations includes trust in people and law enforcement agencies, attitude to goals and values, assertive behavior, compliance with legal norms, and attitude to law as readiness to comply with the rights of others based on the principles of justice and equality. A regression analysis revealed the following socio-psychological predictors of attitude to law: legal consciousness (legal realism), assertive behavior, protection of human rights by law enforcement officers, and compliance with the principles of interpersonal justice. Legal cynicism proved to have a negative impact on attitude to law.